Lifestyle modification for weight control - Wadden, Thomas (Henry Stewart Talks, 2007)
Lifestyle modification: treatment examines antecedents, behaviour and consequences, Diet: self-monitoring, dietary plans and portion-controlled meals, Exercise: weight loss in low activity vs. high activity, Lifestyle vs. programmed activity, Status of behavioural treatment for obesity, Weight loss maintenance, Diabetes prevention programme, Look AHEAD study (Action for Health in Diabetes), Combining behavioural and pharmacological treatments, Responding to the obesity epidemic